2018
DOI: 10.1017/s0376892918000322
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence Hunting with Mixed-Breed Dogs Reduces Hunting Pressure on Sensitive Amazonian Game Species in Protected Areas

Abstract: Hunting is a major threat to wildlife, and the use of dogs for subsistence hunting may significantly impact wildlife. I assessed the impacts of hunting with dogs by comparing the assemblages of species hunted by the Huni Kuin with and without dogs in indigenous lands in southwestern Brazilian Amazonia. I also assessed whether Huni Kuin agreements on hunting with dogs can be effective for conservation. Huni Kuin hunters with dogs rely on a different assemblage of prey than those without dogs; the former strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The effectiveness of hunting deer with trained dogs [65,66] is evident in the passage above. In this same interview, Mauro and Duda said that when hunters sight deer tracks and release their dogs to chase it, they already know which direction the deer will flee, based on the "spine" [hillslope] in that location.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The effectiveness of hunting deer with trained dogs [65,66] is evident in the passage above. In this same interview, Mauro and Duda said that when hunters sight deer tracks and release their dogs to chase it, they already know which direction the deer will flee, based on the "spine" [hillslope] in that location.…”
Section: Resultsmentioning
confidence: 98%
“…This passage, in particular, indicates the great complexity involved in the interaction and communication between a hunter and his dog. This intimate and ancient bond between man and dog [62][63][64] is an element without which the local praxis of hunting cannot be well understood, nor its impact on the local fauna [65,66]. The man-dog-deer relationship in the context of hunting will be explored in detail below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these dogs is very serious given the possibility of declining natural populations of various animals, as well as being a gateway to many contagious diseases for wild species (Vilela & Guedes, 2017). On the other hand, a study evaluating the impact of hunting dogs on indigenous lands in the southwestern Brazilian Amazon concluded that, in terms of conservation, there is no reason to ban hunting with dogs (Constantino, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, lessons learnt from practical experience show that this has limited impact, and particularly when it only focuses on militarization (Duffy et al, 2019). The reasons for failure are numerous and include corruption, lack of resources from the government to exercise sovereignty in remote locations where hunting takes place, lack of political will to prioritize law enforcement regarding wildlife crimes, lack of alternatives to replace supply, high level of dependency on wildmeat for households living in extreme poverty, and a demand which is difficult to downsize due to the high value that consumers are ready to pay (Bennett, 2011;Wellsmith, 2011;Challender and MacMillan, 2014;Cooney et al, 2017;Swan, 2017;Constantino, 2019b). In addition, the intrinsic nature of laws and regulations on hunting is also at the heart of the failure, but little is said about the urgency to reform and adapt the regulatory framework, particularly with regards to hunting for food.…”
Section: Introductionmentioning
confidence: 99%